2014
DOI: 10.1111/jcal.12078
|View full text |Cite
|
Sign up to set email alerts
|

Supporting multimedia learning with visual signalling and animated pedagogical agent: moderating effects of prior knowledge

Abstract: An experiment examined the effects of visual signalling to relevant information in multiple external representations and the visual presence of an animated pedagogical agent (APA). Students learned electric circuit analysis using a computer-based learning environment that included Cartesian graphs, equations and electric circuit diagrams. The experiment was a 2 (visual signalling, no visual signalling) × 2 (visual APA presence, no visual APA presence) between-subjects design, resulting in four experimental con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 91 publications
7
57
0
Order By: Relevance
“…That learning via CSA has a profound impact on subsequent problem-solving is attributed to intensive human-computer interactions built in the CSA learning module. (Johnson, Ozogul, & Reisslein, 2014), virtual reality (Merchant et al, 2013, augmented reality (Bressler & Bodzin, 2013), and remote virtual laboratories (Potkonjak et al, 2016). Such technologies are particularly attractive to many contemporary tech-savvy students, as they promote active learning and can be easily and widely adopted at both formal and informal education sites with no requirement for expensive physical facilities and instrumentations.…”
mentioning
confidence: 99%
“…That learning via CSA has a profound impact on subsequent problem-solving is attributed to intensive human-computer interactions built in the CSA learning module. (Johnson, Ozogul, & Reisslein, 2014), virtual reality (Merchant et al, 2013, augmented reality (Bressler & Bodzin, 2013), and remote virtual laboratories (Potkonjak et al, 2016). Such technologies are particularly attractive to many contemporary tech-savvy students, as they promote active learning and can be easily and widely adopted at both formal and informal education sites with no requirement for expensive physical facilities and instrumentations.…”
mentioning
confidence: 99%
“…The agent with gestures did not produce significant effects compared to agent-only property, since it failed to demonstrate the expressiveness effect. Conversely, Lusk and Atkinson (2007), Johnson et al (2014), Baylor et al (2003) and Schroeder et al (2013) all demonstrated that agents using locomotion, gaze, and gesture to direct learners' attention are more effective than static ones.…”
Section: The Agent Effectsmentioning
confidence: 91%
“…The embodied agent effect was found in the systems of Atkinson (2002), Dunsworth and Atkinson (2007), Johnson et al (2014) and Moreno et al (2001). In their work, Johnson et al (2014) argues that both the agent's image and visual signaling improve the performance of students with low prior knowledge.…”
Section: The Agent Effectsmentioning
confidence: 97%
See 1 more Smart Citation
“…Mayer and DaPra (2012) showed that an agent using social cues in the form of gestures, facial expressions and eye-gaze led to better learning outcomes than the same agent lacking these social cues. Likewise, Johnson et al (2015) found that an agent who pointed agent compared to an agent that did not point had a beneficial impact on learning outcomes -for students with low prior knowledge.…”
Section: Characteristics Of Digital Tutees In Relation To Student Leamentioning
confidence: 96%